BORDER MALARIA: INCREASE AND CHALLENGES CONTROL IN HUONG HOA AREA, QUANG TRI PROVINCE IN 2025 (Vietnam Journal of Community Medicine, 2026)
Border-related population mobility–associated malaria is a current priority; assessing increasing trends, interventions, and challenges is essential to interrupt local transmission and support Vietnam’s malaria elimination roadmap.Objectives: Objective 1: To assess the increasing trend and epidemiological characteristics of malaria in Huong Hoa District in 2025. Objective 2: Describe the interventions and challenges in managing malaria related to cross-border population mobility in Huong Hoa.Methods: A descriptive cross-sectional study of malaria cases recorded in Huong Hoa during the first 10 months of 2025.Results: A total of 47 cases were recorded, occurring from June to October, with a peak in August (20 cases). Males accounted for 55.3%; working-age individuals 66.0%; the Van Kieu ethnic group 76.6%; and forest/farm work 59.6%. P. vivax predominated (93.7%); indigenous cases accounted for 63.8%, while imported cases from Lao PDR accounted for 21.3%; local transmission was identified, concentrated in A Doi. Interventions included proactive screening for early case detection, strengthened vector control, health communication, and strict treatment management (DOT), particularly for P. vivax.Conclusion: Malaria increased in Huong Hoa in 2025, mainly affecting males aged >15 years, those engaged in forest/farm work, and was predominantly caused by P. vivax. Interventions achieved some effectiveness; however, cross-border mobility, adherence to prolonged P. vivax treatment, and limited preventive behaviors remain challenges requiring sustained, coordinated action.
Keywords: Border malaria, Huong Hoa